2017
DOI: 10.4238/gmr16019492
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of DNA damage and anticarcinogenic activity of Activia<sup>®</sup> in a preclinical model

Abstract: ABSTRACT. Colorectal cancer is a global public health issue. Studies have pointed to the protective effect of probiotics on colorectal carcinogenesis. Activia ® is a lacto probiotic product that is widely consumed all over the world and its beneficial properties are related, mainly, to the lineage of traditional yoghurt bacteria combined with a specific bacillus, DanRegularis, which gives the product a proven capacity to intestinal regulation in humans. The aim of this study was to evaluate the antigenotoxic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(55 reference statements)
1
7
1
Order By: Relevance
“…The study used a commonly recommended probiotic yogurt which has been evaluated in randomized trials for gastrointestinal ailments such as constipation 16 . While preclinical studies have identified a potential anticancer effect of this probiotic yogurt in murine models of colon cancer, we failed to show any difference across arms in regard to cancer progression or gastrointestinal toxicity 17 . Longitudinal stool microbiome profiling showed B. animalis , the key component of the probiotic yogurt supplement, was prevalent in the probiotic‐supplemented arm but nearly absent in the probiotic‐restricted arm.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The study used a commonly recommended probiotic yogurt which has been evaluated in randomized trials for gastrointestinal ailments such as constipation 16 . While preclinical studies have identified a potential anticancer effect of this probiotic yogurt in murine models of colon cancer, we failed to show any difference across arms in regard to cancer progression or gastrointestinal toxicity 17 . Longitudinal stool microbiome profiling showed B. animalis , the key component of the probiotic yogurt supplement, was prevalent in the probiotic‐supplemented arm but nearly absent in the probiotic‐restricted arm.…”
Section: Discussioncontrasting
confidence: 60%
“…16 While preclinical studies have identified a potential anticancer effect of this probiotic yogurt in murine models of colon cancer, we failed to show any difference across arms in regard to cancer progression or gastrointestinal toxicity. 17 Longitudinal stool microbiome profiling showed B. animalis, the key component of the probiotic yogurt supplement, was F I G U R E 1 Hierarchical cluster of top 20 taxa identified in all metagenomic samples identified by MetaPhlAn2. 14,15 Bray-Curtis clustering and heatmap generation were performed using hclust2.…”
Section: Discussionmentioning
confidence: 99%
“…However, these percentages cannot allow to establishing correlation between the time of supplementation and the levels of chemoprevention. This fact is also described for other functional foods such as inulin 4 , glutamine 31 and the commercial product Activia® 32 .…”
Section: Resultsmentioning
confidence: 64%
“…Regarding the demutagenic and bioantimutagenic activities mentioned before, both can be identified for each protocol. The Pre-treatment protocol may indicate activity by both demutagenesis and bioantimutagenesis 32 . Previous DNA exposure to the flaxseed diet could induce cell enzymes to repair the damage caused by DMH, for example, indicating bioantimutagenesis activity.…”
Section: Methodsmentioning
confidence: 99%
“…The present experimental design is common in the field area [ 14 , 19 , 21 , 24 , 25 , 26 ] as it might indicate the mechanism of action of dietary fiber in the prevention and/or repair of DNA damage and other biomarkers for cancer. Thus, pre-treatment and simultaneous treatment protocols suggest a preferentially demutagenic effect and the post-treatment protocol a bioantimutagenesis effect [ 27 , 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%